2016
DOI: 10.1002/smll.201601696
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Multifunctional WS2/WOxNanodots for Chelator-Free89Zr-Labeling and In Vivo PET Imaging

Abstract: While position emission tomography (PET) is an important molecular imaging technique for both preclinical research and clinical disease diagnosis/prognosis, chelator-free radiolabeling has emerged as a promising alternative approach to label biomolecules or nanoprobes in a facile way. Herein, starting from bottom-up synthesized WS2 nanoflakes, we fabricate a unique type of WS2/WOx nanodots, which could function as inherent hard oxygen donor for stable radio-labeling with Zirconium-89 isotope (89Zr). Upon simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Recently 2D metal oxides, particularly tungsten oxide (WO 3 ), have drawn significant research interest from both academic and technological viewpoints because of their novel properties and some notable applications. WO 3 possesses different crystal structures, exotic electronic properties, tunable band gap, and high specific surface area which are key factors for sensors, catalysts, transistors, photodetectors, solar cells, electrochromic devices, lithium ion batteries, and energy storage applications . The crystal structure of WO 3 comprises with corner sharing of “WO 6 octahedrons” and exhibits various distinguishable crystal forms such as poorer symmetric monoclinic, triclinic, tetragonal and higher symmetric orthorhombic, hexagonal, and cubic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently 2D metal oxides, particularly tungsten oxide (WO 3 ), have drawn significant research interest from both academic and technological viewpoints because of their novel properties and some notable applications. WO 3 possesses different crystal structures, exotic electronic properties, tunable band gap, and high specific surface area which are key factors for sensors, catalysts, transistors, photodetectors, solar cells, electrochromic devices, lithium ion batteries, and energy storage applications . The crystal structure of WO 3 comprises with corner sharing of “WO 6 octahedrons” and exhibits various distinguishable crystal forms such as poorer symmetric monoclinic, triclinic, tetragonal and higher symmetric orthorhombic, hexagonal, and cubic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on WS 2 and TiS 2 also revealed some interesting results and suggest potential bioapplications . WS 2 nanosheets could be used not only for PTT but also as a nanocarrier for PDT owing to their 2D structure that provided large surface area to load photosensitizer agents .…”
Section: Interactions Between Other 2d Materials and Biointerfacesmentioning
confidence: 97%
“…Furthermore, WS 2 :Gd 3+ ‐PEG can convert NIR light into heat for PTT as well as facilitate ionizing irradiation‐induced tumor ablation via enhanced radiation therapy (RT). Zirconium‐89 ( 89 Zr) can also be anchored onto PEG‐modified WS 2 /WO x (WS 2 /WO x ‐PEG) nanodots via a chelator‐free method . Such 89 Zr incorporated nanodots are excellent as PET contrast agents, for in vivo imaging of tumors after intravenous injection or mapping of draining lymph nodes upon local administration.…”
Section: Interactions Between Other 2d Materials and Biointerfacesmentioning
confidence: 99%
“…The principle of these preoperative imaging technologies and scope of application are not demonstrated in this review, but it is worth noting that CT and MRI provide imaging with anatomy information, while PET and SPECT provide functional information. [178,[220][221][222] [197][198][199][200] Grimm et al reported the 89 Zr-radiolabeled iron oxide NPs ( 89 Zr-ferumoxytol) for LN mapping by PET/MRI with high resolution and sensitivity.…”
Section: Preoperative Imaging For Precision Surgerymentioning
confidence: 99%